FUNGSI TUTURAN EKSPRESIF DALAM FILM NGERI-NGERI SEDAP SUTRADARA BENE DION - Kiki Widyawati; Asnawi (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2023)
Expressive language is not only used in direct communication between individuals, but it also appears in films through dialogues between characters. These dialogues are based on real-life communication, which typically occurs between speakers and their addressees. The movie